Determinants of honey producer market outlet choice in Chena District, southern Ethiopia: a multivariate probit regression analysis - Kassa Tarekegn; Jema Haji; Bosena Tegegne (Agricultural and Food Economics, 2017)
Marketing outlets choice is one of the most important farm household decisions to sell their produce and has a great impact on household income. Though the study area has great potential of honey production, the farmers in the study area faced the marketing problem in choice of appropriate honey market outlets. This study was therefore carried out to analyze determinants of honey producers' market outlet choice decisions in Chena district. A total of 154 honey-producing households were surveyed, and the data obtained were analyzed by using multivariate probit model. The results show that most sampled households in the study area sell their honey to cooperative outlet as compare to other outlets. The results of the econometric model show the dependency of household level marketing decisions as a strategy to maximize their incomes in the long term. The model results also reveal that the quantity of honey sold, frequency extension contact, beekeeping experience, distance to nearest market, market information about each outlet, cooperative membership, and trust in buyers determine market outlet choice decision of honey producers in the study area. Expanding equal accessibility of infrastructures, establishing honey collection centers in potential production areas, increasing the frequency of extension contact, and organizing additional beekeepers into honey cooperatives is suggested.
Keywords: 330; Honey; Market outlets; Multivariate probit; Chena district